Advisers and their Students in the 21st Century: challenges for the graduate programs - Nóbrega, Maria Helena da (Educação e realidade, 2018)
This article aims to analyze how the academic mentoring is characterized, precisely the relationship between advisers and their students. Besides the participant observation, the methodology is based on the theoretical-bibliographic study of the subject. The analysis takes into account the orientation in the field of languages, to be precise: Portuguese for speakers of other languages, justified by the increasing internationalization of the Brazilian universities. The result shows lack of research, especially in Brazil. As a conclusion, the author recommends narrowing the relation among research, teaching and mentoring, adapting it to the 21st century, as well as providing specific training for the advisor.